1994
DOI: 10.1073/pnas.91.4.1214
|View full text |Cite
|
Sign up to set email alerts
|

Two-site binding of C5a by its receptor: analternative binding paradigm for G protein-coupled receptors.

Abstract: The guanine nucleotide-binding proteincoupled receptor superfamily binds a vast array of biological messengers including lipids, odorants, catecholamines, peptides, and proteins. While some small molecules bind to these receptors at a single interhelical site, we find that the binding domain on the receptor for the inflammatory protein C5a is more complex and consists of two distinct subsites. This more elaborate motif appears to be an evolutionary adaptation of the simpler paradigm to which a second interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

16
196
2
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(215 citation statements)
references
References 31 publications
16
196
2
1
Order By: Relevance
“…NSPs have been shown to proteolytically reduce the expression of several cell-surface molecules involved in immunity, including CXCR1 (IL-8RA), CR1, CD16, CD43, and TNFRII, but their impact on C5aR expression has not been investigated. Proteolytic cleavage and inactivation of C5aR has been demonstrated by a variety of endogenous and exogenous proteases, including an endogenous metalloprotease, activated by the action of Loxosceles spider venom sphingomyelinase D, a serine protease from Porphyromonas gingivalis, and a metalloprotease from venom of the spider Plectreurys tristes (22)(23)(24). Direct proteolysis and inactivation of C5aR by an endogenous protease has not been demonstrated so far; however, a reduced chemotactic response to C5a after NE and CG treatment has been reported (25).…”
mentioning
confidence: 99%
“…NSPs have been shown to proteolytically reduce the expression of several cell-surface molecules involved in immunity, including CXCR1 (IL-8RA), CR1, CD16, CD43, and TNFRII, but their impact on C5aR expression has not been investigated. Proteolytic cleavage and inactivation of C5aR has been demonstrated by a variety of endogenous and exogenous proteases, including an endogenous metalloprotease, activated by the action of Loxosceles spider venom sphingomyelinase D, a serine protease from Porphyromonas gingivalis, and a metalloprotease from venom of the spider Plectreurys tristes (22)(23)(24). Direct proteolysis and inactivation of C5aR by an endogenous protease has not been demonstrated so far; however, a reduced chemotactic response to C5a after NE and CG treatment has been reported (25).…”
mentioning
confidence: 99%
“…It has two major regions important for ligand binding (15). The first, interacting with the core of C5a, is in the extracellular N-terminal domain, and the second, interacting with the C terminus of C5a, is poorly characterized and lies within the transmembrane helices (possibly helix V) of the receptor.…”
mentioning
confidence: 99%
“…The first, interacting with the core of C5a, is in the extracellular N-terminal domain, and the second, interacting with the C terminus of C5a, is poorly characterized and lies within the transmembrane helices (possibly helix V) of the receptor. Several studies have indicated that ligand interaction with the putative transmembrane binding site but not the N terminus of the receptor is responsible for the induction of cellular responses, like chemotaxis and enzyme release from neutrophils (15)(16)(17)(18). Subsequently, a number of C5a C-terminal analogs interacting with the second, "effector" site of the receptor and possessing different agonistic properties were generated (19 -21).…”
mentioning
confidence: 99%
“…As evidence for the role of the first-site interaction, truncation of the N terminus reduces the affinity of the receptor for full-length ligand, but preserves the efficacy of hexapeptide analogs of the C5a C-terminal tail (8). Conversely, the small molecule L-584,020 competes with full-length C5a but not with hexapeptides (8), suggesting that L-584,020 inhibits binding but not activation.…”
mentioning
confidence: 99%
“…Conversely, the small molecule L-584,020 competes with full-length C5a but not with hexapeptides (8), suggesting that L-584,020 inhibits binding but not activation. Furthermore, NMR spectroscopy has shown that the structure of the isolated C5aR N terminus is altered by incubation with C5a, suggesting that the N terminus of the receptor interacts with the ligand (11).…”
mentioning
confidence: 99%